A survey of challenges and solutions for the integration of renewable energy in datacenters. (March 2022) - Rostirolla, G.; Grange, L.; Minh-Thuyen, T.; Stolf, P.; Pierson, J.M.; Da Costa, G.; Baudic, G.; Haddad, M.; Kassab, A.; Nicod, J.M.; Philippe, L.; Rehn-Sonigo, V.; et al.
Abstract: As more and more activities are moving online, the need for datacenters is increasing which raises their energy consumption and the resulting greenhouse gas emissions. The supply of datacenters with renewable energy is often seen as the main solution to this nexus. However, multiple challenges are posed by their integration. Solutions to these challenges, mainly in the form of flexibility and energy efficiency, require multidisciplinary skills. As a consequence, this article aims to review scientific efforts in several complementary disciplines: electrical engineering, computer science, control system engineering and operations research. It covers datacenter architecture, infrastructure sizing and resource management on both information and energy sides. Conclusions on current progresses are drawn and challenges that remain to be addressed are listed as well. Highlights: Challenges and solutions for using of renewable energy in datacenters are surveyed. Related work on modeling, sizing and managing power and IT resources is presented. Flexibility on power and IT to tackle generation intermittency is investigated. Open research challenges regarding infrastructure and predictive methods are listed.